2013
DOI: 10.1177/1753944713513221
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and hormonal patterns of untreated essential hypertension in men and women

Abstract: Background Knowledge of hemodynamic factors accounting for the development of hypertension should help to tailor therapeutic approaches and improves blood pressure control. Few data exist regarding sex differences of hemodynamic factors contributing to hypertension progression among untreated non-diabetic prehypertensive (PreHyp), Stage I and II subjects as define by the Joint National Commission-7 guidelines (JNC-7). Methods We utilized non-invasive impedance cardiography, applanation tonometry, and plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
3
21
1
Order By: Relevance
“…We confirmed the previous observations that women, having comparable brachial BP, characterized with higher CBP than men. 3,12,13 The differences concerned CSBP and CPP, whereas CDBP was not influenced by sex. Peripheral amplification of systolic BP and PP in women, expressed as brachial to central difference, was almost half of this reported in men.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We confirmed the previous observations that women, having comparable brachial BP, characterized with higher CBP than men. 3,12,13 The differences concerned CSBP and CPP, whereas CDBP was not influenced by sex. Peripheral amplification of systolic BP and PP in women, expressed as brachial to central difference, was almost half of this reported in men.…”
Section: Discussionmentioning
confidence: 88%
“…6 Although women with AH are more aware of the need of treatment and visit physicians more frequently 2 they do not reach satisfactory control of BP. 3 The question whether, and how, the antihypertensive therapy should be sex-adjusted remains without satisfactory answer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study contradicted the previous medical belief that the impact of HPN is the same in both sexes and concluded that a high BP may be significantly more dangerous in women than in men [45] . Knowledge of the hemodynamic factors that account for the development of HPN should help to tailor therapeutic approaches and improve BP control.…”
Section: Personalized Management Of Hpn In Womenmentioning
confidence: 64%
“…20,21 In addition, recent data identify accelerated vascular disease in women compared with men for the same range of uncontrolled HT. 22 Although the mechanisms and impact of gender differences on HT control are not fully known, these data support the concern that poor BP control in aging females may have long-term effects that vary from men. Our data suggest that BP recidivism is a more common finding in elderly women.…”
Section: Discussionmentioning
confidence: 87%